2017
DOI: 10.3390/w9080627
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Runoff Control Legislation and Active, Beautiful, Clean (ABC) Waters Design Features in Singapore

Abstract: Storm water management in Singapore has always been a challenge due to intense rainfall in a flat, low-lying and urbanised catchment. PUB's (Singapore's National Water Agency) recent runoff control regulation limits the runoff coefficient to 0.55 for developments larger than or equal to 0.2 ha. The use of Active, Beautiful, Clean (ABC) Waters design features are encouraged to attain peak runoff reduction. Hence the paper focuses on (i) determining the actual hydrological response regime of Singapore using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…In the early 2000s, via the further integration of BMP techniques and LID principles, "Green Infrastructure" (GI) was implemented across the Western hemisphere to manage stormwater and improve environmental, social, and economic sustainability [35]. Similar concepts have influenced Asia-Pacific cities, such as the "Active Beautiful and Clean Waters" (ABC) programme initiated in Singapore in the mid-2000s, which aims to promote more active, beautiful, and clean-living environments for the public using "Blue-Green Infrastructure" (BGI) measures [36]. In the early 2010s, several UK cities stated the aspiration to become a "Blue-Green City" (BGC) [37], which is a city that aims to recreate a more naturally oriented water cycle in its urban environment by merging its management of the urban water cycle with its management of public green spaces and corridors [38].…”
mentioning
confidence: 99%
“…In the early 2000s, via the further integration of BMP techniques and LID principles, "Green Infrastructure" (GI) was implemented across the Western hemisphere to manage stormwater and improve environmental, social, and economic sustainability [35]. Similar concepts have influenced Asia-Pacific cities, such as the "Active Beautiful and Clean Waters" (ABC) programme initiated in Singapore in the mid-2000s, which aims to promote more active, beautiful, and clean-living environments for the public using "Blue-Green Infrastructure" (BGI) measures [36]. In the early 2010s, several UK cities stated the aspiration to become a "Blue-Green City" (BGC) [37], which is a city that aims to recreate a more naturally oriented water cycle in its urban environment by merging its management of the urban water cycle with its management of public green spaces and corridors [38].…”
mentioning
confidence: 99%
“…Nevertheless, the optimisation results reveal to us that the efficiency and effectiveness of the original precinct can be very much improved to yield more cost-effective designs with lower effective runoff coefficients. The runoff coefficients adopted for the various land uses were based on a study on the runoff coefficients for Singapore, which found that runoff coefficients are sensitive to the slope of a catchment as well as the land use [36]. The study by Goh et al [36] improved upon the runoff coefficient recommendations for various land use types in Singapore's COP on Surface Water Drainage [7] and developed runoff coefficients for different land use types that also took into account the slope of the catchment.…”
Section: Results Of Orifice Outlet and Gravel Storage Optimisationmentioning
confidence: 99%
“…The runoff coefficients adopted for the various land uses were based on a study on the runoff coefficients for Singapore, which found that runoff coefficients are sensitive to the slope of a catchment as well as the land use [36]. The study by Goh et al [36] improved upon the runoff coefficient recommendations for various land use types in Singapore's COP on Surface Water Drainage [7] and developed runoff coefficients for different land use types that also took into account the slope of the catchment. The runoff coefficients and percentage imperviousness adopted for the various land uses in our study are as summarised in Table A4.…”
Section: Results Of Orifice Outlet and Gravel Storage Optimisationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although neither GI, BGI, nor ecosystem services are mentioned, the ABC Waters Program exemplifies a shift from gray infrastructure to BGI in urban water management, showcasing a BGI-building program for a high-density city. Despite the ABC Waters Program has been carried out for more than a decade and has received several international awards, its literature remains limited to the technical aspects of stormwater management (e.g., Goh et al 2017;Quek et al 2015). Lim and Lu (2016) provide a comprehensive review of the program, but only as a stormwater management program.…”
Section: Introductionmentioning
confidence: 99%